RESULTS OF VACUUM-ATMOSPHERIC DRYING OF LARGE-DISPERSED FOOD MATERIALS - Abdizhapparova Bakhytkul Telkhozhaevna; Khanzharov Nurlan Serikbayevich; Ospanov Bakhytzhan Orazalievich; Pankina Ilona Anatolyevna; Kumisbekov Serik; Islam Karlygash Sapibullakyzy (Academic Scientific Journal of Chemistry, 2019)
In the given article the results of researches of heat and mass transfer for vacuum-atmospheric drying of large-dispersed food materials as crushed tubers of topinambour, potato, apple and peas are considered. Optimal regimes of vacuum-atmospheric drying of the given materials are developed. Results of vacuum and atmospheric drying of large-dispersed materials are studied. Depending on height of layer of drying material, pressure of medium into vacuum camera, temperature level of drying the numerical values of coefficients of heat and mass transfer and equations of heat and diffusion Nusselt criterions are received. Comparison on adequacy to real conditions is conducted in order to check the criterion equations. Meanings of experimental and calculated data of heat and mass transfer coefficients have satisfied convergence.